Epidemiology of neonatal encephalopathy and hypoxic-ischaemic encephalopathy. - Kurinczuk, J; White-Koning, M; Badawi, N (2010)
Neonatal encephalopathy (NE) is the clinical manifestation of disordered neonatal brain function. Lack of universal agreed definitions of NE and the sub-group with hypoxic-ischaemia (HIE) makes the estimation of incidence and the identification of risk factors problematic. NE incidence is estimated as 3.0 per 1000 live births (95%CI 2.7 to 3.3) and for HIE is 1.5 (95%CI 1.3 to 1.7). The risk factors for NE vary between developed and developing countries with growth restriction the strongest in the former and twin pregnancy in the latter. Potentially modifiable risk factors include maternal thyroid disease, receipt of antenatal care, infection and aspects of the management of labour and delivery, although indications for some interventions were not reported and may represent a response to fetal compromise rather than the cause. It is estimated that 30% of cases of NE in developed populations and 60% in developing populations have some evidence of intrapartum hypoxic-ischaemia.